사염화탄소에 의한 간손상에 대한 황백의 간보호 효과 연구 - 곽창근(Chang Geun Kwak); 김재은(Jae Eun Kim); 최달영(Dall Yeong Choi); 정한솔(Han Sol Jeong); 신상우(Sang Woo Shin); 주명수(Myoung Su Joo); 하기태(Ki Tae Ha) (동의생리병리학회지, 2011)
We evaluated the hepatoprotective activity of crude hot-water extracts of the traditional Korean medicinal herb, Phellodendri Cortex (PC; Bark of Phellodendron amurense RUPR.), in an experimental model of hepatic damage induced by carbon tetrachloride ($CCl_4$). The serum marker of liver damage, sGOT, sGPT and sALP, were significantly decreased in the liver of the PC treated rats, compared with that of $CCl_4$ treated group. The histological observation of liver section of rats, showed the same protective effect of PC treatment. And the protective activity of PC was more significant in the post-treated group than pre-treated group. The significant decrease of malodialdehyde and increase of glutathion, catalase activity were observed in the liver homogenate of PC treated rats. Based on these findings, it is suggested that PC has potent hepatoprotective effects and the mechanism of the protection may be related to antioxidation pathways.